Developing Indonesian E-Module Assisted by Storytelling Podcast Containing Character Education - Ugahari, Vendi Pandu; Kuntoro, K; Lazasniti, Septiana (Proceedings International Conference on Education Innovation and Social Science, 2024)
The aim of this paper was to develop an Indonesian e-module with the help of a storytelling podcast containing character education in elementary schools. The study used ADDIE model research and development (R&D) method. The research phase was designed in five stages, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The study result was a product of Indonesian e-module and storytelling podcast containing character education. ADDIE model R&D method showed that e-module was effective in increasing students' knowledge. This Indonesian e-module assisted by a storytelling podcast containing character education is very suitable in student learning in elementary schools.